Analysis of the Readiness of Primary Health Center Nurses in Encountering Community Stigma during the COVID-19 Pandemic - Siregar, Tatiana; Ratnawati, Diah (JURNAL INFO KESEHATAN, 2022)
The COVID-19 outbreak has resulted in public fear of transmitting infection. Nurses in dealing with the COVID-19 outbreak also obtained stigmatized due to discrimination received by COVID-19 sufferers. The objective of the study is to identify the dominant factor to determine the occurrence of stigma experienced by nurses when caring for COVID-19 patients. The research design was qualitative and quantitative, with a sample of 121 Primary Health Center nurses who were performed by convenience sampling. Data analysis with Multiple Linear Regression presented that overall, there was a significant correlation between knowledge in preventing COVID-19, Personal Ability and Organizational Ability to stigma from society experienced by nurses with ANOVA or F test results (229.427) with p = 0.000. Morever, there is a strong and significant relationship between knowledge, self-efficacy and organizational ability to community stigma (R Square = 0.964). The dominant factor that affects stigma as seen from the t-test is self-ability = 14,828 (p=0.001) followed by organizational ability= -8,790 (0.001) and knowledge = 5.050 (p=0.001). It was concluded that the limitations of human resources and special infrastructure for people with COVID-19 were the trigger for the occurrence of stigma. It is hoped that the maintenance of well-being among health workers is at the forefront by beginning at the policy-making level to offer enhanced support for health workers who play a critical role during large-scale disease outbreaks. The psychological implications are mostly negative and urgently need greater attention to be mitigated, potentially through the involvement of psychologists, given better awareness and education. It is expected that further researchers can explore the phenomenon of the experience of nurses who suffer from COVID-19 in dealing with the stigma that occurs to them.